Different Histological Stains Used for Assessing the Morphology of Cementum - A Review - Shruthi Devi1 , K. R. Don2 , Karthik Ganesh Mohanraj3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Cementum is a unique least mineralised tissue with only little information known on cementogenesis. Hencevarious stains have been identified to view the morphology of cementum. Cementum is critical for attachmentof the tooth to the surrounding periodontal ligament (PDL). This study aims to review various stains usedfor assessing the cementum morphology.The study setting is a review where the information about the topicis obtained from various search engines like pubmed and google scholar by searching the keywords and thestudy was made. The cementum is a distinct and unique mineralized hard tissue which shares many similarproperties with the dentin and bone. There are various methods of histotechniques for studying morphologyand development of cementum. Upon overview of various histological approaches for studying and stainingof cementum through light microscopy are H&E, Toluidine Blue, Alcian blue, Picrosirius red, etc. Bonesialoprotein, osteopontin, DMP1, etc., are the staining methods using immunohistochemistry. Cementumannulations are used in forensic analysis to determine the age of the body. Hence, studying about these stainsmight help to understand the morphology of cementum deeply and thus give accurate details.